A proposed guidance program to reduce the anxiety level of mothers of the pupils who are going to pass the baccalaureate exam: اقتراح برنامج ارشادي للتخفيف من مستوى القلق لدى أمهات التلاميذ المقبلين على شهادة البكالوريا (المجلة العربية للعلوم و نشر الأبحاث, 2017)
The study aimed to reveal the effectiveness of a guidance programme to reduce the anxiety levelof mothers of the pupils who are going to pass the baccalaureate exam at Sidi A'baz secondary school inthe wilaya of Ghardaia,Algeria.To achieve the study objectives,it was selected a sample of 35 mothers thathad the highest grades on the scale of anxiety.The study was conducted on a sample of six mothers whoaccepted to attend the sessions of the guidance programme.The researcher used two tools:The Tyler'sanxiety scale whose psychometric properties were remeasured and a guidance programme to reduce thelevel of anxiety,prepared by the researcher, consisted of seven sessions for four weeks;the duration of thesession ranged from 50 to 90 minutes.In order to answer the study questions,it was used the MannWhitney Test.After the statistical analysis,the study results showed statistically significant differencesbetween the mean scores of the mothers' group in the pre test and the post test on the anxiety scalein favour of the post test.